ANALISIS NILAI RASIO LIKUIDITAS & SOLVABILITAS TERHADAP KEPUTUSAN MENYIMPAN DANA PADA PERUSAHAAN PT. BANK RAKYAT INDONESIA (PERSERO) TBK - Fadlan, Fikri; Marisa, Issa; Nuraeni, Putri; Gunardi, Gunardi; Kurniawan, Sandy (Jurnal Ilmiah Magister Ilmu Administrasi, 2024)
Indonesia's economy is driven largely by the banking sector. Banking encourages investment and economic growth through bank credit playing an important role in this regard. helping small and medium enterprises (PKM). PKM is an important economic resource that helps governments finance economic development and infrastructure projects. Business people, governments and other users of financial reports can assess the financial condition and performance of banks with the help of capital financial ratio analysis by looking at last year's liquidity and solvency ratio data. This analysis can also determine the ideal value of liquidity and solvency ratios and explain the consequences that occur if a bank has a calculated level of liquidity and solvency ratios below the ideal value relative to the level of fulfillment of obligates to investors